'Why do they need to punish you more?': Women's lives after imprisonment. Issue 2 (3rd April 2017) - Agboola, Caroline
ABSTRACT: This article reports on a study which examined the experiences of women in South Africa after imprisonment. Using in-depth interviews, the experiences of 13 women ex-prisoners who were imprisoned in South African prisons were examined. It emerged that some of the participants of the study experienced unemployment, stigma and discrimination, as well as the psychological effect of imprisonment after incarceration. The psychological effect of imprisonment that some of the participants reported was reflected in the inability of this category of women to make friends and in their display of some of the habits that they learned in prison, such as staying in the dark even though they had no reason to after incarceration. It was revealed that unemployment increased significantly among the participants, and some of the participants were victims of stigma and discrimination from their families, in particular, and society, in general. The feminist pathways approach was used to explain the participants' criminal offending and how some of their experiences after imprisonment may have resulted in recidivism. Further, female-headed households was identified as a pathway unique to the offending behaviour of South African women.